The influence of neuromarketing: machine learning based empirical analysis - Muktadir, MD. Abdullah Al; Malek, Shamsul; Hossain, Zakia (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.